Expression of TIM-1 in patients with glioma and its correlation with clinicopathological features: Expression of TIM-1 in patients with glioma - Zhang, Yonghu; Chen, Ping (Cellular and Molecular Biology, 2022)
The objective of this research was to investigate the expression of TIM-1 in patients with glioma and its correlation with clinicopathological features. The clinical data of 79 patients with gliomas in our hospital from February 2016 to February 2020 were selected as the research objects of this experiment. TIM-1 detection kit, ELISA and eliysion kit were used to detect TIM-1. The expression of TIM-1 was detected by an automatic immunohistochemical analyzer. Results revealed that the expression of TIM-1 in glioma tissue was abnormal, and its level was significantly higher than that in normal tissue adjacent to the tumor. The high level of TIM-1 expression in gliomas was correlated with KPS grade and histological grade., The expression level of TIM-1 in glioma tissue can affect the survival rate of patients and become one of the independent risk factors of glioma. In conclusion, the histological grade and KPS grade of glioma are related to the high-level expression of TIM-1, which not only suggests that TIM-1 is involved in the occurrence and malignant progression of glioma but also suggests that the malignant change of glioma has a high risk